Effect of age and gender on the expression level of IL-6 and thyroid hormones TSH, T3, T4 in thyroid patients. (Journal of the College of Basic Education, 2026)
The thyroid gland is an endocrine gland responsible for the synthesis and secretion of thyroxine (T4) and triiodothyronine (T3) (thyroid hormones), which play a key role in regulating metabolism as well as development and growth, Thyroid disorders a disease affecting the thyroid gland, resulting from an abnormality resulting from excessive or insufficient activity. This steady aimed To evaluate the level of immune factor Interleukin-6 (IL-6) and thyroid hormones; Thyroid Stimulating Hormone (TSH), Triiodothyronine (T3), Thyroxin (T4) in thyroid patients. Material and method This study was conducted by collecting (50) blood samples from thyroid patients and (50) individuals as a control group, aged between (30-65) years. Interleukin 6 (IL-6) levels were measured using ELISA, and thyroid hormones (TSH, T3, and T4) were measured. Samples were collected from April 2024 to September 2024, Patient data (age, gender, smoking, family history) were collected, Results The results showed that the highest infection rate was in the age group (<=50) as it reached (50%), and the highest infection rate was in males as it reached (60%), and the highest expression rate of ((IL-6) was in the age group (>=60) as it reached (21.2198 ± 7.4022, 33.4202 ± 7.43473) respectively, and the results showed a significant difference in the expression of (IL-6) in females as it reached (16.2766 ± 6.87162) in patients compared to control (3.4363 ± 1.20474) (p≤0.001), The results also showed a significant difference in the expression of (TSH), which reached (5.3053 ± 7.84264) in patients compared to healthy people (2.3450 ± 1.98495) (p≤0.01). The results also showed a significant difference in the expression of (TSH) in patients, which reached (7.3205 ± 9.63679) in females. The results also showed a significant difference in the expression of (T3) in patients in all age groups (p≤0.05), The results also showed a significant difference in T3 expression across different age groups (p≤0.05). Regarding T4 expression, the results showed a significant difference in T4 expression among patients (6.7440 ± 1.42115) compared to healthy controls (7.9500 ± 3.08097) (p≤0.01), The results also showed a significant difference in )T4( expression across different age groups (p≤0.001). Statistical Analysis Statistical analysis was performed using using spss version 25.ConclusionThe current study showed that the highest incidence rate was in the age group (<=50) and the highest expression rate of (IL-6) was in the age group (>=60) and there was a significant difference in the expression of (IL-6) in females compared to the control group. The study showed a significant difference.The study also showed a significant difference in TSH expression in patients compared to the control group. There was also a significant difference in TSH expression in female patients. The age groups of patients also showed a significant difference in T3 expression in patients across all age groups.